Avaliação do teor e análise qualitativa do ágar das espécies Gelidiella acerosa (FORSSKÅL) Feldmann and G. Hamel (GELIDIALES, RHODOPHYTA) e Gracilaria domingensis (KÜTZING) Sonder ex Dickie em costões rochosos dos municípios de Ilhéus e Uruçuca - Santos, Janaina Pires (2011)
Gelidiella acerosa and Gracilaria domingensis are red algae producing agar. These kinds of genera are highlighted in the production of phycocolloids world. Agar is a polysaccharide whose chemical structure consists of two parts: agarose and agaropectin that are present in cell walls of these seaweeds. Variations in the type of agar can occur in one species and therefore are considered as chemical family of agaranas. Both the yield and chemical characterization of agar show us important parameters of commercial interest. The results for content and quality of agar were obtained from samples collected in two shores at the Ilhéus and Uruçuca. The agar content of Gracilaria domingensis species was higher when compared to those found for Gelidiella acerosa, in the same place such variations can be derived from such factors as: the formation of the stem, the extraction and ecophysiological conditions. Data for quality of the gel revealed that the specie Gracilaria domingensis was highlighted by a high content of 3.6 anhydrogalactose, nevertheless offered a product less power compared to gel of Gelidiella acerosa, suggesting less demanding commercial applications, related to the sector food. On the other hand, the specie Gelidiella acerosa presented an agar gel with high quality that meets standards of market demand. This study was pioneered about the investigation of the economic potential of species of Gracilaria domingensis and Gelidiella acerosa to southern Bahia and represents the starting point for further studies on the feasibility of deployment of cultivation in the region.